The Practice of Warung Jablay in Hulu Sungai Utara Regency in The Perspective of Sociology of Islamic Law - Pahrul Pahrul; Ahdiyatul Hidayah (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
The Warung Jablay business in the North Hulu Sungai Regency area has disturbed many residents. Basically, this kind of night girl stall has the same function as other stalls, but often because of the presence of young girls with sexy and skimpy clothes and differences in the way of service provided and differences in customer segmentation which are mostly filled by young people. So, there are many things that violate morals and religion in the field, and this is not in line with the teachings of Islam. This study aims to map how the practice of Warung Jablay in Hulu Sungai Utara is associated with Perspectives in the Sociology of Islamic Law, because Hulu Sungai Utara Regency is famous for its high religious area and is known as Bertaqwa City. This research is field wise with a qualitative descriptive approach. The results of this study found that people believe that the behavior of some people who run a stall business like this is driven by economic factors and desires. In addition, the community also considered the behavior of Warung Jablay workers to be out of bounds and violated moral, social, and religious norms.